Analisis Beban Kerja Mental pada Pekerja Kantor Menggunakan Metode NASA-TLX - Lestari Widyastuti; Tangguh Dwi Pramono (Applied Business and Administration Journal, 2024)
The existence of company demands to achieve targets makes employees work excessively to overtime. This makes employees experience pressure, causing a mental workload that has an impact on decreasing work performance and productivity. This study aims to measure the amount of mental workload and what indicators most influence the mental workload by using the National Aeronautics and Space Administration Task Load Index (NASA-TLX) method for office workers at PT X. The sample in this study, namely a number 20 people with purposive sample data collection and analyzed using the NASA-TLX method. The results of the data analysis show that the average value of mental workload experienced by PT X employees is 80.367 which is included in the very high category and the dominant indicator influencing this value is the Level of Effort and Performance, namely 19.55 and 19.083. The recommendations suggested as material for consideration for handling the high workload on office workers, namely conducting work evaluations to see how employees are performing.